Perancangan ulang desain tata letak fasilitas produksi di CV. Macarindo Berkah Group menggunakan metode ARC dan CRAFT - Nita Kuswardhani; Dinasty Alfajar Rizky (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
CV Macarindo Berkah Group is one of the food processing industries (Snacks) located in Jember, with the product being processed is macaroni. The company wants to develop an efficient production system so that the total distance of material transfer, the total moment of movement and the cost of material handling (OMH) are optimal. The problem in the arrangement of production facilities there is unused space between departments and back and forth flow so that the production line is getting longer. The layout used is the product layout to reduce the total moment of displacement. The method used is CRAFT with input from the initial layout and ARC to show the degree of relationship between departments. The results are that there is an efficiency after improvement for the total distance of material transfer to 42.5 m from 48.5 m with an efficiency value of 12.4%, for the total moment of material transfer to be 2,365,6 m/day from 2,834.4 m/day. days with an efficiency value of 16.5% and for the total cost of material handling (OMH) to Rp. 68,516 from Rp. 82,368.3 with an efficiency value of 16.8%.